Anti-terrorism courts' convictions in trials of sectarian-terrorism crimes: A case study of the Punjab province of Pakistan. Issue 4 (December 2022) - Umar, Muhammad; Khan, Naeemullah
Sectarian activists in Pakistan are occasionally arrested by law enforcement agencies in sectarian-terrorism crimes but very rarely convicted by the courts. Contemporary research mainly relates slow convictions in sectarian crimes to defects in the state's criminal justice system. But this article connects anti-terrorism courts' (ATCs) slow convictions and large-scale acquittals in sectarian-terrorism crimes to vague anti-terror laws, judges' and witnesses' security concerns and the incompetence of the prosecution and judges. The article applies the mixed method of research by using data from personal interviews, online sources, newspapers, research journals, articles and books. It argues that undefined anti-terrorism laws, judges' security concerns and sectarian activists' terrorization of judges and eyewitnesses add to the ATCs' slow convictions in sectarian-terrorism crimes in the Punjab. Moreover, prosecution and judges' incompetence and their inclination towards Islamic principles in judgements show bias in the application of sectarian-terrorism related laws that have been causing large-scale acquittals in the ATCs.